Bridges.org - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Bridges.org is an international non-profit organization that supports initiatives focusing on improving access and getting technology used, in order to strengthen communities, democratic institutions, free press and local economies, working with - instead